2022
DOI: 10.14349/sumapsi.2022.v29.n2.3
|View full text |Cite
|
Sign up to set email alerts
|

The Infidelity Scale: Psychometric properties and gender invariance among Portuguese adults

Abstract: Introduction: Infidelity is a breach of trust or a crossing of the boundaries of the primary relationship and it influences intimate relationships. It can be categorised as either sexual or emotional infidelity. In Portugal, there have been few studies on this subject using suitable instruments. Objective: This study aimed to analyse the factor structure, psychometric properties, and gender invariance of the Infidelity Scale (IS) in Portuguese adults. Method: The sample comprised 660 Portuguese adults (455 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Consequently, with improved mental health against life's pressures, their optimal performance level throughout life can be maintained (Chamzadeh Ghanavati et al, 2022). The results align with the prior research (Almeida & Ifrim, 2023;Chamzadeh Ghanavati et al, 2022;Kianpour Barjoee et al, 2022;Sooreh et al, 2023;Taherkhani et al, 2023), which reported the positive impact of positive thinking skills training on cognitive and behavioral changes. Positive thinking can be accentuated by considering ways of viewing 103 E-ISSN: 3041-8518 events and is a significant source of motivation for individuals to continue their daily lives.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consequently, with improved mental health against life's pressures, their optimal performance level throughout life can be maintained (Chamzadeh Ghanavati et al, 2022). The results align with the prior research (Almeida & Ifrim, 2023;Chamzadeh Ghanavati et al, 2022;Kianpour Barjoee et al, 2022;Sooreh et al, 2023;Taherkhani et al, 2023), which reported the positive impact of positive thinking skills training on cognitive and behavioral changes. Positive thinking can be accentuated by considering ways of viewing 103 E-ISSN: 3041-8518 events and is a significant source of motivation for individuals to continue their daily lives.…”
Section: Discussionsupporting
confidence: 91%
“…In general, the anterior and posterior cingulate cortex and parts of the right hemisphere play a special role in thoughtful problem-solving (Kianpour Barjoee et al, 2022). Almeida and Ifrim (2023) in their research titled "Psychometric Benefits of Positive Thinking Skills Scale among Portuguese Adults," tested 220 adults aged 18 to 62. They stated that positive thinking leads to more positive emotions, adaptive behaviors, and better problem-solving.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Con rmatory Factor Analysis (CFA) supported the unifactorial structure proposed in the original version (3,29) and in Turkish (28), Arabic (54) and Portuguese (55) adaptations. This nding underscores the reliability and validity of the PTSS, a rming its relevance across various cultural contexts.…”
Section: Discussionmentioning
confidence: 56%